Religious literacy of Australia's Gen Z teens: diversity and social inclusion - Halafoff, Anna (Journal of beliefs and values, 2020)
Australia is a culturally, religiously and linguistically diverse country, however, learning about the religious dimensions of this superdiversity is inadequately reflected in the national school curriculum, notwithstanding recent attempts to address this at the state level in Victoria. Debates regarding the role of religion in school have raged across the country for decades and have impeded the introduction of learning about diverse worldviews and religions, and even research on this topic. Competing views of Australia's national identity, as a multifaith and/or secular and/or Christian nation, continue to affect both policy and curriculum in Australia, and thereby the level of religious literacy of its citizens. Using data from a national study of young Australians and their worldviews, this research investigates levels of religious literacy and appreciation of religious diversity of Generation Z' Australians, for whom superdiversity is the norm. In doing so, it concludes that Australian curricula must evolve to include more content on diverse worldviews and better reflect the lived experiences of younger generations. This would in turn increase religious literacy and interreligious understanding in Australia. This study may also be instructive for those countries grappling to adjust to similar demographic and societal changes, challenges and opportunities.